Sumber dan Kualitas Pakan Serta Produksi Kambing Peranakan Etawah Di Kotamadya Banda Aceh - Al Qudri (Agricultural Faculty, 2002)
ABSTRACT.A study on source and quality of feed and production of Etawah goats was conducted from June to November, 1997. Nine respondents who raise Peranakan Etawah goats were interviewed. The goats were investigated and measured for body size. The respondents were live in three different villages, i.e, three from Ule Lheu, one from Lambung, two from Punge, one from Peulanggahan and two from Rukoh. The result showed that source of fed were obtained from grass in the back yart, native pasture, by product of banana, fruits, vegetables and palatable leaves. The quality of feed was relatively good due a relatively high content of protein. Ratio of male tp female was 1 : 1.65. Kid production was about 190 percent / yard. Body size were better than kids that are raised in villages in Aceh Barat regency.